A CRITICAL SIZE DEFECT MODEL IN THE RADIUS OF RABBITS - MINTO, B. W.; GONÇALVES NETO, J. A.; SPRADA, A. G.; QUARTERONE, C.; SARTORI, M. R.; DE ALCÂNTARA, B. M.; HESPANHA, A. C. V.; USCATEGUI, R. A. R. (Ars Veterinaria, 2020)
This study aimed to characterize a preclinical model of critical size defect (CSD) in the radius of rabbits.Twenty adults (> 7 months), female, New Zealand Rabbits, weighing between 3,5 to 5 Kg were used. They underwent a 1.5 cm long ostectomy of the diaphysis of the radius, starting 2 cm from the carpus joint. Radiographic analyses were performed at 15, 30, 60, and 90 days postoperatively, in order to evaluated bone callus formation, periosteal reaction, and bone bridge formation.The methodology allowed to precisely create bone defects of 1.5cm. Over time, no bone deposition was found at 15 days, but mild bone callus formation was observed in three animals after 60 days postoperative. At 90 days postoperatively only one rabbit presented bone consolidation radiographically, the others presented non-union. The critical bone defect proposed in this study was satisfactory, feasible with very low risk of complications.